Do sofredor ao vencedor: tempo, poder e felicidade nas revistas Lições Biblícas (1975-1999) - Nunes, Viviane Teixeira Lima (2022)
This research proposes an analysis of discourses on happiness and well-being in Lições Bíblicas magazines, a periodical published quarterly by Casa Publicadora das Assembleias de Deus - CPAD. Having as a target audience the members of the Assembleias de Deus, these magazines are used as didactic support in Sunday Schools, a space for Christian formation in which it seeks to teach, from a determined reading of the Bible, how to be a Christian in all aspects of life. It is, therefore, a form through which the leadership of the movement seeks to build an identity for the group, putting into question not only the practices, but also the subjectivities of the readers, seeking to reconstruct and reinvent them in the name of relationship with the sacred. In these pages, pleasure, happiness and well-being are ideas mobilized in defense of certain positions. Such mobilizations are often conflicting and complex, related to interpretations of modernity, discipline and control of the body. It was noted that, over the years, the discourse of the leadership of the Assembleias de Deus in Brazil was being modified and the uses of happiness, pleasure and well-being were intensified. The idea of the suffering believer and therefore worthy of salvation was giving way to the idea of the winning believer. These changes are related to the advent of what Lipovetsky (2007) called a ―hyperconsumption society‖, in which discourses about happiness occupy a central place. Such issues are also crossed by technologies of power such as discipline and control, as well as by biopower proposed by the philosopher Michel Foucault (2008). The period studied ranges from 1975 to 1999, when the first Resolution on Uses and Customs passed by the Convenção Geral das Assembleias de Deus no Brasil, a document that dealt with different practices from which church members should abstain and indicates how this group interpreted the world and officially positioned itself in relation to it. In carrying out this work, in addition to the Lições Bíblicas magazines, resolutions and minutes of meetings of the Convenção Geral das Assembleias de Deus no Brasil, as well as other periodicals in circulation in the period, are analyzed as sources. Considering happiness as an idea disputed over time, the study of its meanings and uses in this print helps to understand the conflicting relationships of this religious group with the changing world, with time and with the other.